Homologous Recombination Pathway Alternation Predicts Prognosis of Colorectal Cancer With Chemotherapy - Lin, Yan; Liao, Xiaoli; Zhang, Yumei; Wu, Guobin; Ye, Jiazhou; Luo, Shanshan; He, Xinxin; Luo, Min; Xie, Mingzhi; Zhang, Jinyan; Li, Qian; Huang, Yu; et al. (Frontiers in Pharmacology, 2022)
Background Chemotherapy is the basic treatment for colorectal cancer (CRC). However, colorectal cancer cells often develop resistance to chemotherapy drugs, leading to recurrence and poor prognosis. More and more studies have shown that the Homologous recombination (HR) pathway plays an important role in chemotherapy treatment for tumors. However, the relationship between HR pathway, chemotherapy sensitivity, and the prognosis of CRC patients is still unclear. Methods We collected 35 samples of CRC patients after chemotherapy treatment from Guangxi Medical University Cancer Hospital, then collected mutation data and clinical prognosis data from the group. We also downloaded Mondaca-CRC, TCGA-CRC cohorts for chemotherapy treatment and Samstein-CRC cohorts for immune check point inhibitors (ICIs) from the cbioportal and TCGA databases. Result We found that HR-MUT patients are less likely to experience tumor metastasis after receiving chemotherapy. Additionally, our univariate and multivariate cox regression models showed that HR-MUT can be used as an independent predictor of the prognosis of chemotherapy for CRC patients. The KM curve showed that patients with HR-MUT CRC had significantly prolonged OS time (log-rank P = 0.017; hazard ratio (HR) = 0.69). Furthermore, in the Samstein-CRC cohort, we found that HR-MUT could also be used as an independent predictor of the prognosis of the CRC patients undergoing immunotherapy treatment. Compared to HR-WT, HR-MUT has a significantly lower IC50 value with several chemotherapeutic drugs. Pathway enrichment analysis further revealed that the HR-MUT displayed a significantly lower rate of DNA damage repair ability, tumor growth, metastasis activity, and tumor fatty acid metabolism activity than HR-WT, though its immune response activity was notably higher. Conclusions These findings indicate that HR-MUT may be a relevant marker for CRC patients receiving chemotherapy, as it is closely related to improving OS time and reducing chemotherapy resistance.